PENERAPAN MENGARANG TERBIMBING MODEL KWL (KNOW, WANT, LEARNED) UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI - Sutarna, Nana (Profesi Pendidikan Dasar, 2016)
Skill of student writing narrative essay in class IV Elementary School Cengal III, District Kuningan, yet reached at the expected level. One of the ways that deems appropriate to solve the problem was through the application of learning guided writing by KWL model with picture media. This research used classroom action research with using of qualitative approach. Classroom action research design used refers to Kemmis and Mc Taggart model started with planning, action, observation, and reflection. The research instrument used were the student activity observation guidelines, interview, field notes, and questions. Then the collected data were processed and analyzed. While checking the validity of the data using triangulation techniques, member checks, and expert opinion. Through the application of learning guided writing by KWL model with picture media in narrative essay, student learning outcomes class IV elementary school Cengal III can increase. This was evidenced by the increasing number of students who were otherwised completed on each cycle, started from preliminary data as many as three students or 15%, the first cycle increased to 9 people or 45%, on the second cycle increased to 18 people or 90%.